Ultrasound-guided erector spinae plane block versus rhomboid intercostal block for postoperative analgesia following thoracotomy - KAYNAR ŞİMŞEK, AYNUR (My University, 2022)
Aim: For the thoracotomy pain relief, opioids, thoracic paravertebral and epidural interventions are frequently used practices. In recent years, interfascial blocks such as the erector spinae plan block (ESPB) and rhomboid intercostal block (RIB) have started to be used for analgesia. We aimed to compare the postoperative analgesic effect of ESPB, RIB, and a control (C) group in pain management after open thoracotomy. Material and Methods: This is a single-centered randomized controlled trial. A total of 75 patients were included in the study in three groups as the ESPB, RIB and control (C) groups. Under general anesthesia, in block groups, blockage was performed with 20 ml 0.25% bupivacaine. In Group C, no procedures other than the standard postoperative analgesia protocol were performed. The amount of postoperative analgesic consumption by the patients, and visual analogue scale (VAS) values were recorded. Results: In group ESPB and RIB, the mean 24-hour tramadol consumption was 124 +/- 29.08 mg and 116 +/- 28.65 mg, respectively (p>0.05). In Group C, the consumption was 204 +/- 44.06 mg, significantly higher than in group ESPB and group RIB (p=0.004). The VAS values (p<0.05) and the numbers of patients needing rescue analgesic (p=0.048) were lower in groups ESPB and RIB than in group C. There was no significant difference between group ESPB and group RIB in any of these parameters Discussion: ESPB and RIB were similar and they are more effective than the control group, whereas the former did not have superiority over each other.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & İÇECEK; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Analgesia; Block; Thoracotomy